Saccadic and smooth pursuit eye movements attenuate postural sway similarly - Rodrigues, Sérgio Tosi [UNESP]; Polastri, Paula Fávaro [UNESP]; Carvalho, Jamile Cristina [UNESP]; Barela, José Angelo [UNESP]; Moraes, Renato; Barbieri, Fabio Augusto [UNESP] (Elsevier B. V., 2015)
Saccadic eye movements reduce body sway, yet visually pursuing a moving dot seems to increase body sway. However, how these two types of eye movements affect postural control remains ambiguous, particularly for smooth pursuit eye movements. The aim of this study was to examine the effects of saccade and smooth pursuit eye movements on body sway magnitude during low and high frequencies. Ten young adults (19.5 ± 1.9 years) participants were required to stand upright, barefoot for 70s using a bipedal stance, with feet hip width apart, fixating or pursuing a target that was displayed on a monitor positioned 100 cm away from their eyes. Each participant performed three trials using both types of eye movements, in particular, slow and fast saccades, and slow and fast smooth pursuit movements. Body sway was obtained using reflective markers attached to a participant's head and trunk, which were recorded by two video cameras. The results indicated that body sway was reduced during both saccadic eye movements and smooth pursuit movements when compared to fixation, independent of visual frequencies. These results suggested similarities in the control of saccades and smooth pursuit on postural control.
Keywords: Eye movements; Postural control; Saccades; Smooth pursuit